Liberated waste: heritage and materiality at Robben Island and Constitution Hill, South Africa. Issue 3 (4th March 2019) - Jethro, Duane
ABSTRACT: In post-apartheid South Africa the state instrumentalised the idea of heritage to advance a project of reconciliation and nation building. Heritage was framed as an inherent good, facilitating symbolic restitution through foregrounding black public histories and fostering a national culture based on the common ownership of heritage resources. This article evaluates this framing of heritage through analysis of the reworking of material remains recovered at two sites of apartheid era incarceration and their different paths to heritage 'status'. First, it discusses the recovery and rebranding of the fence from Robben Island as an artistic and design commodity. Second, it describes the demolition and recycling of building material from the Old Fort Prison in Johannesburg to build the Constitutional Court. Using ruination as a theoretical entry point, the article shows how the heritage significance of these remains was brought out through engaged interpretation that explicitly linked the material to a dominant, reconciliatory post-apartheid heritage narrative. It was then circulated in different economies of cultural, political and economic value, and put to work to generate commercial profit or to promote constitutional justice. Showing these divergent outcomes, the article critiques the utility of a reconciliatory framing of heritage for purposes of inclusive nationalism.